Caturan politik pelbagai kaum di Tanah Melayu 1946-1957 - Ishak Saat, (Penerbit UKM, 2010)
Political cooperation between the different races in the Malay Peninsula started in a period following the Second World War. Given the existing challenges of that time, some had succeeded and some had come to a dead end. The Malays‟ political maturity and openness started with the joint cooperation of Pusat Tenaga Rakyat (PUTERA) with THE All Malayan Council of Joint Action (AMCJA) in 1947. This political tolerance succeeded in giving birth to the People‟s Constitution. However, it was promptly rejected by the British as it was put forward by radical group. Thereafter, another political cooperation, this time of the moderate parties, involving the United Malayan National Organization (UMNO) and Malayan Chinese Association (MCA) gave birth to what is famously called PERIKATAN in 1949. In the run-up to the Independence, there was another failed effort at political cooperation among the radical groups, known as SOCIALIST FRONT. Eventually, the political cooperation managed to prove to the British that the Malays and non-Malays can exist together and politically cooperate in order to fulfill their common aspiration of achieving independence. Thus, this article will explore the early history of multi-racial political cooperation and tolerance in Tanah Melayu.